Upaya meningkatkan Karakter Religus Siswa melalui metode Inquiry di TPQ Asaqwa sawangan depok - Abdi Prayudi (ASWAJA: Jurnal Pendidikan dan Keislaman, 2023)
This research aims to enhance the religious character of students at TPQ Asaqwa through the implementation of the inquiry method. The Classroom Action Research (CAR) approach was used with students actively participating. The inquiry method was adopted as a learning approach involving students in the processes of investigation, problem-solving, and self-reflection on religious values. The research findings indicated a significant improvement in the religious character of students after applying the inquiry method in research cycles. In cycles 1 and 2, involving 10 students, there were 6 students who had not yet reached the set target. However, after implementing the inquiry method, students demonstrated a better understanding of religious values. Furthermore, in the subsequent cycles, there was a notable increase of 30% in students' religious character. Within the range of cycles 40%-70%, students exhibited a better understanding of religious values, active engagement in religious activities, and increased self-awareness of the importance of practicing religious teachings in their daily lives following the implementation of the inquiry method in research cycles. These results highlight the effectiveness of the inquiry method in enhancing the religious character of students at TPQ Asaqwa.